In vitro Measurement of CMP-Sialic Acid Transporter Activity in Reconstituted Proteoliposomes - James Cahill; Shivani Ahuja; Matthew Whorton (Bio-Protocol, 2020)
Nucleotide-sugar transporters (NSTs) facilitate eukaryotic cellular glycosylation by transporting nucleotide-sugar conjugates into the Golgi lumen and endoplasmic reticulum for use by glycosyltransferases, while also transferring nucleotide monophosphate byproducts to the cytoplasm. Mutations in this family of proteins can cause a number of significant cellular pathologies, and wild type members can act as virulence factors for many parasites and fungi. Here, we describe an in vitro assay to measure the transport activity of the CMP-sialic acid transporter (CST), one of seven NSTs found in mammals. While in vitro transport assays have been previously described for CST, these studies failed to account for the fact that 1) commercially available stocks of CMP-sialic acid (CMP-Sia) are composed of ~10% of the higher-affinity CMP and 2) CMP-Sia is hydrolyzed into CMP and sialic acid in aqueous solutions. Herein we describe a method for treating CMP-Sia with a nonselective phosphatase, Antarctic phosphatase, to convert all free CMP to cytidine. This allows us to accurately measure substrate affinities and transport kinetics for purified CST reconstituted into proteoliposomes.